Prenatal detection of structural cardiac defects and presence of associated anomalies: a retrospective observational study of 1262 fetal echocardiograms. (10th March 2015) - Mone, Fionnuala; Walsh, Colin; Mulcahy, Cecelia; McMahon, Colin J.; Farrell, Sinead; MacTiernan, Aoife; Segurado, Ricardo; Mahony, Rhona; Higgins, Shane; Carroll, Stephen; McParland, Peter; McAuliffe, Fionnuala M.
Abstract Objective The aim of this study is to document the detection of fetal congenital heart defect (CHD) in relation to the following: (1) indication for referral, (2) chromosomal and (3) extracardiac abnormalities. Method All fetal echocardiograms performed in our institution from 2007 to 2011 were reviewed retrospectively. Indication for referral, cardiac diagnosis based on the World Health Organization International Classification of Diseases tenth revision criteria and the presence of chromosomal and extracardiac defects were recorded. Results Of 1262 echocardiograms, 287 (22.7%) had CHD. Abnormal anatomy scan in pregnancies originally considered to be at low risk of CHD was the best indicator for detecting CHD (91.2% of positive cardiac diagnoses), compared with other indications of family history (5.6%) or maternal medical disorder (3.1%). Congenital anomalies of the cardiac septa comprised the largest category (n = 89), within which atrioventricular septal defects were the most common anomaly (n = 36). Invasive prenatal testing was performed for 126 of 287 cases, of which 44% (n = 55) had a chromosomal abnormality. Of 232 fetuses without chromosomal abnormalities, 31% had an extracardiac defect (n = 76). Conclusions Most CHDs occur in pregnancies regarded to be at low risk, highlighting the importance of a routine midtrimester fetal anatomy scan. Frequent association of fetal CHD and chromosomal and extracardiac pathology emphasises the importance of thorough evaluation of any fetus with CHD. © 2015 John Wiley & Sons, Ltd.